The Effects of Organic and Inorganic Fertilizers on Red Chili Plants - I Gusti Nyoman Arthanawa; I Nyoman Astika; I Ketut Darmawan; Dewa Putu Semara Yana; Yohanes Parlindungan Situmeang; I Dewa Nyoman Sudita (Warmadewa University Press, 2022)
Red chili is one of the commodity crops grown in Indonesia. One of the factors that affect the production of red chili plants is fertilization. The application of organic fertilizer affects the yield and growth of red chili plants. This study aims to determine the response of the growth and development of red chili plants to the application of organic and inorganic fertilizers combined with biochar. This study was carried out at the Experimental Garden of the Local Waste Processing Site in Kusamba Village, Klungkung Regency, and the Laboratory of the Agrotechnology Study Program, Faculty of Agriculture Warmadewa University from March to November 2021. Soil and fertilizer testing were carried out at the Soil Science Laboratory, Udayana University. The study used an experimental method, the experimental design used was a one-factor randomized block design with 4 replications/block. The parameters observed were plant height, number of leaves, stem diameter, number of fruit per plant, fruit weight per plant, and fruit weight harvested per hectare. Based on the data obtained, the type of fertilizer treatment had a very significant effect on all observed variables except for plant height at 21 DAP per plant, the number of leaves at 21 DAP per plant, and the number of leaves at 28 DAP per plant had a significant effect on the treatment given. The application of NPK fertilizer gave the best results on all parameters except for the stem diameter parameter. On the stem diameter parameter, the application of asri nature fertilizers gives the best result. Control treatment (without fertilizer) gave the lowest yield in all observations.